A note on reliefs for traveling expenses to work - Matthias Wrede (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 1999)
Assuming that higher traveling expenses reduce traveling time, this paper considers reliefs for traveling expenses to work when a distorting wage tax is levied. While the decision on traveling expenses would not be distorted if traveling costs were completely deductible, taxation would still not be neutral with respect to the leisure-consumption choice. Moreover, the paper shows that second-best optimum taxation requires less than complete deductibility of traveling expenses to work.
Keywords: H21; H24; 330; income taxation; reliefs; traveling expenses to work; optimum taxation; Kosten; Steuerbegünstigung; Lohnsteuer; Optimale Besteuerung; Theorie; Pendelverkehr